Image encryption : a communication perspective - 574432 Abd el-Samie, Fathi E.; Ahmed, Hossam Eldin H., author; Elashry, Ibrahim F., author; Shahieen, Mai H., author; Faragallah, Osama S., author; El-Rabaie, El-Sayed M., author; Alshebeili, Saleh A. (Boca Raton, Florida : CRC Press, Tayllor & Francis Group, 2014)
"This book covers image encryption principles as well as different encryption techniques with different purposes are covered. The image encryption topic is treated from a communication perspective. It is expected to have readers from the undergraduate and post graduate communities. This book describes, evaluates, and compares, with respect to security level and encryption speed algorithms that fall into the representative image encryption techniques, nav̐e, position permutation, value transformation, substitution-transposition and selective techniques. It will assist application developers in selection of the encryption that best fulfills the application requirement"--provided by publisher